PERTUMBUHAN AWAL AKSESI DOYO HASIL DOMESTIKASI (Early Growth Of Doyo Accession Domestication Reseults) - Candra Catur Nugroho; Erwin Arief Rochyat (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2018)
Doyo (Curculigo latifolia) which grows wild in nature is one of the important plants in East Borneo which was many benefit, one of them as as raw material of ulap doyo’s woven fabric. This research was aimed to perform domestication stages by looking at the initial vegetative growth process of doyo plants in one location. Doyo accession was obtained at 15 location points from 6 sub-districts (Tenggarong, Bangun City, Muara Wis, Anggana, Bongan and Jempang) which were then carried out domestically on experimental land in Bukit Biru Village, Tenggarong District. This research used a randomized block design with a single factor were doyo accession (6 accessions). Observation data were analyzed with F test (α=5%) and continued DMRT (Duncan Multiple Range Test) using SAS v. 11.6. The results showed that the highest percentage of live doyo accession in polybags was obtained at Bongan accession (85.16%), while the lowest was obtained at Kota Bangun accession (32.42%). Meanwhile, when planted in the field of research, based on the results of variance showed that the treatment of accession had a significant and very significant effect on the parameters of height increase of plants at 1 and 2 month after planting (WAP), increase in stem diameter, length of leaf midrib, leaf stalk length, leaf length, width leaves, and the number of new leaves at 1-3 MAP, but not significantly different from the parameters of plant height increase at 3 MAP and number of tillers. The highest leaf length was obtained at Bongan accession, while the highest leaf width ang number of new leaves were obtained at Tenggarong accession. Keywords: Domestication, doyo accession, East Borneo